The Relationship Between Interpersonal Communication and Toxic Relationships in Adolescents in Cimanggis Sub District Depok City - Hanifa Insyiradeasti (Badan Perencanaan Pembangunan Penelitian dan Pengembangan Daerah Kabupaten Bogor, 2024)
The basis of a successful relationship is communication, so if the communication carried out by the sender and receiver of the message is not successful, then the relationship will not run well, which is likely to arise a toxic relationship. Toxic relationships occur a lot among teenagers, the number of violence against women is increasing every year. But not only women are victims, men can also be victims of toxic relationships. The purpose of this study was to determine the relationship between interpersonal communication and toxic relationships in adolescents in Cimanggis District, Depok City. This research was conducted in Cimanggis sub-district, Depok City. This research uses quantitative methods. This study has 2 variables, namely Interpersonal Communication Barriers with Signs of Toxic Relationship. The data collection technique used by researchers is Non-Probability sampling with an accidental sampling approach. The data collection technique in this study used a questionnaire. The results of this study indicate that there is a significant relationship between Interpersonal Communication Barriers and Toxic Relationship in Adolescents in Cimanggis sub-district, Depok City. Indicators with the strongest correlation are Physical Barriers with Violence to bind partners, as well as Emotions and Aggressive. When they are in the long distance relationship phase, the perpetrator does not hesitate to commit acts of violence, threats, and control the victim because of the fear of excessive loss experienced by the perpetrator. They also often fight, because they are at a distance so that communication is sometimes unsuccessful, so negative emotions often arise.Keywords: characteristics; depok city; interpersonal communication; toxic relationship